RED GIANT BRANCH OF THE METAL POOR GLOBULAR CLUSTERS: II. BUMP, TIP, AND DISTANCE OF NGC 1904 - J.W. Kim; Y. Choi; S. H. Chun; J. Jung; A. Kang; Y.-J. Sohn (Journal of Astronomy and Space Sciences, 2006)
From the BV images of the metal-poor globular cluster NGC 1904 obtained with the 2K CCD camera equipped on the BOAO 1.8m telescope, we construct (B - V, V) color-magnitude diagram of the cluster. The apparent V magnitudes of the RGB bump and tip have been measured from the luminosity function of the iteratively selected RGB stars in NGC 1904. Theoretical absolute Mv magnitudes of the RGB bump and tip are estimated using the Yonsei-Yale isochrones. The distance modulus of NGC 1904 has been derived by comparing the observed apparent V magnitude with the estimated absolute Mv magnitude of the RGB bump and tip.